Aktivitas Digital Public Relations Melalui Website Pramuka.Id. - Damayanti, Revina; Astuti, Dyah Rahmi; Sarbini, Ahmad (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to describe how Digital Public Relations Activities through the 3C concept (Content, Computing, and Communication) on the Pramuka.Id website, in an effort to provide information and provide a forum for Scout members in Indonesia with constructivism paradigms, interpretative approaches, research research methods. qualitative descriptive, as well as data collection through in-depth interviews, passive participatory observation, and documentation. The results of research on Digital Public Relations Activities conducted by the National Quarterly Information Center through a three-stage process on the 3C concept, namely 1) (Content) through a long process such as creating content tables, selecting incoming information, and editing manuscripts 2) (Computing) in management, content management, and search engine search using CMS and SEO 3) (Communication) conducted by the team to the audience using synchronous chat and asynchronous methods.